The effect of octreotide in acute nonvariceal upper gastrointestinal bleeding: A randomized, double-blind, placebo-controlled trial - Masoud Abrishami; Payam Peymani; Marziyeh Zare; Kamran B Lankarani (Wolters Kluwer Medknow Publications, 2020)
Objective: Nonvariceal upper gastrointestinal bleeding (NUGIB) is a common cause of hospitalization and is associated with considerable mortality and morbidity. Octreotide has been shown to be an effective treatment in the control of variceal UGIB. Theoretically, octreotide could be effective in the treatment of other types of bleeding ulcers. Methods: This randomized, double-blind, placebo-controlled trial was carried out on patients with NVUGIB who had been admitted to two referral centers in Shiraz, Iran. Patients were randomized to two groups: Group A (n = 58) received octreotide and Group B (n = 58) received a placebo. Patients in both groups received pantoprazole 40 mg as an initial dose, then 40 mg every 12 h intravenously. In addition to the pantoprazole, patients in Group A received 100 μg octreotide subcutaneously every 8 h for 72 h or until they were discharged. Patients in Group B received pantoprazole and a placebo at the same dose schedule. Findings: There were no statistically significant differences between Groups A and B in terms of mortality (0 vs. 5.17%; P = 0.21,) rebleeding rate (5.17% vs. 1.72%; P = 0.5), blood transfusion requirement (1.65 ± 0.47 units vs. 1.70 ± 0.45 units; P = 0.45), length of hospital stay (1.96 ± 1.00 days vs. 1.65 ± 0.84 days; P = 0.44), and need for surgery (1.72% vs. 1.72%; P = 0.7). Conclusion: The results showed that use of subcutaneous octreotide as an adjuvant treatment did not have a beneficial effect on the treatment of NVUGIB.